2000
DOI: 10.1046/j.1464-410x.2000.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of renal function in patients with spinal cord injury

Abstract: Objective To assess the sensitivity of serum creatinine level in detecting clinically important and early deterioration of renal function in patients with spinal cord injury (SCI), and to evaluate the optimal method of determining creatinine clearance in these patients. Patients and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
2
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 11 publications
0
39
2
6
Order By: Relevance
“…In patients with SCI serum creatinine is often signi®cantly decreased as a result of the di use muscle atrophy which commonly accompanies muscle denervation. 24 In patients with SCI normal serum creatinine values could conceal a clinically signi®cant reduction in GFR. Therefore it would be of value to have a simple, safe test to measure renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with SCI serum creatinine is often signi®cantly decreased as a result of the di use muscle atrophy which commonly accompanies muscle denervation. 24 In patients with SCI normal serum creatinine values could conceal a clinically signi®cant reduction in GFR. Therefore it would be of value to have a simple, safe test to measure renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Despite numerous attempts to evaluate the follow-up program, the best method to monitor the renal function in this patient group has not yet been established. 1 A widely used method is the repeated measurement of plasma creatinine (p-creatinine), 2 and equations like the Cockcroft and Gault or MDRD (modification of diet in renal disease) equations have been derived to estimate glomerular filtration rate (GFR) from p-creatinine, age, weight and gender. 3,4 P-creatinine is primarily derived from the metabolism of creatine and phosphocreatine in muscles.…”
Section: Introductionmentioning
confidence: 99%
“…5 Patients with SCI often have a reduced muscle mass because of diffuse muscle atrophy and for this reason the level of p-creatinine is often decreased in such patients. 2 The hypothesis that p-creatinine overestimates the renal function in this patient group has been demonstrated in several studies since the 1980s, [6][7][8][9] but despite this p-creatinine is still a commonly accepted method to monitor renal function in SCI patients. Recognizing this, we wanted to investigate if there was a trend in the level of p-creatinine over a 50-year follow-up period and how well p-creatinine correlated with renal deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…1 Likewise, other studies have found that patients with SCI have significantly low SCr, therefore, CL CG is overestimated. [2][3][4] Such findings may be because of reduced creatinine production caused by diffuse muscle atrophy and persistent immobility. Overestimation of GFR results in dosing renally cleared medications higher than recommended, and this could lead to supratherapeutic vancomycin and AG serum levels leading to adverse drug effects and/or toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, data on the application of MDRD in pharmacokinetic dosing of vancomycin and AG are inconsistent, while there is no data to date on CKD-EPI. [11][12][13][14] The objectives of this study are: (1) to evaluate different methods of estimating GFR compared with patient-specific vancomycin and AG drug clearance (CL DRUG ) in SCI patients, (2) to assess whether there is a difference in the estimation of renal function between anatomical degrees of SCI when compared with CL DRUG and (3) to develop a new equation to more accurately estimate GFR in SCI patients in order to optimize dosing for vancomycin and AG.…”
Section: Introductionmentioning
confidence: 99%